Application of the elements of symbolic computations and automatic code generation technique to the solution of complex PDE problems - Khlybov, Oleg Anatolievich (Computational Continuum Mechanics, 2008)
A software package intended for serial and parallel numerical solution of PDE systems has been developed. The package provides extra flexibility compared to existing commercially available general-purpose computational systems. Although the package is initially aimed at solving CFD problems, it can however be applied to any field where the numerical solution of complex (non)linear PDE systems is required. The closest counterparts such as FreeFEM++, OpenFOAM or FlexPDE are based on similar ideas, but differ in certain important aspects.